PERAN WEST AFRICA COCOA AGRICULTURAL PROJECT (WACAP) DALAM MENGELEMINASI PEKERJA ANAK PANTAI GADING - Ranny Penita Putri; Irwan Iskandar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research aims to find out the role of West Africa Cocoa Agricultural Project (WACAP) for elimination child labour in Cote d’Ivoire. Child labor is one of the social problems which can disrupt the child's mental development and physical development of children. Cote d'Ivoire is one of the country in West Africa that is getting the spotlight related to the numerous child labourers that work under the hazardous conditions on cocoa plantations. In line with the establishment of Harkin-Engel Protocol as one of the effort to eliminate the worst forms of child labour in cocoa and chocolate industry, the involvement of ILO-IPEC is expected to assist in realizing the protocol’s objective. ILO-IPEC established WACAP, a sub-regional program which conducted in four cocoa producing countries and one rice producing country in West Africa.This research uses Pluralism Perspective and Role Concept. It also uses Organization theory and level analysis is Interest Groups. This research uses qualitative method and library research for references by collecting data from books, journals, articles, and news that come from various medias. And applying the questions to the parties who are involve in this research through media.In order to eliminate child labor in Côte d'Ivoire, WACAP has 5 programs. The programs are social awareness, capacity building, social protection, child labor monitoring system and knowledge base and information.Key words : child labour, Cote d’ivoire, WACAP, ILO west africa